مفهوم الحق في الحبس وطبيعته كوسيلة للضمان في القانون المدني: دراسة مقارنة - حماد، شريف رأفت محمد أحمد (جامعة الأزهر - كلية الشريعة والقانون بدمنهور, 2020)
يعد الحق في الحبس- كوسيلة للضمان في القانون المدني- أحد الموضوعات القانونية الهامة الجديرة بالدراسة والتحليل؛ حيث يهدف البحث إلى بيان المقصود به، وأساسه، وطبيعته في القانون المدني والفقه الإسلامي، مع بيان آراء الفقهاء وأحكام المحاكم، مستعينا على ذلك المنهج الاستقرائي التحليلي المقارن. يتألف البحث من فصلين، يتضمن أولهما تعريف الحق في الحبس، وأساسه في القانون المدني والفقه الإسلامي من خلال مبحثين، في حين يشتمل الفصل الثاني على عدة مباحث تبين طبيعة الحق في الحبس في القانون الروماني، والفرنسي، والمصري، وأخيرا الفقه الإسلامي، وينتهي البحث بخاتمة تتضمن أهم النتائج والتوصيات. ويتضح من خلال البحث اتفاق القانون المدني والفقه الإسلامي في تعريفهما لمدلول الحق في الحبس، وكذا اتفاقهما في الأساس الذي أقيم عليه، مع تفرد الفقه الإسلامي بتناول الأساس الأعم "حق الظفرة" ، في حين تباينت آراء الفقهاء والقضاة في طبيعة هذا الحق بين اتجاهات عدة، وقد انتهت الدراسة إلى أنه دفع بعدم القبول من حيث طبيعته، وهو ما أيدته محكمة النقض في بعض أحكامها، وتجدر الإشارة إلى أن الفقه الإسلامي لم يتوقف كثيرا عند بيان طبيعة الحق في الحبس، مكونا بذلك نظرية عامة سبقت التشريع الوضعي بتطبيقه الحق في الحبس باعتباره حق أصلي كلي شامل.
One of the important legal issues worthy of study and analysis is the right to confinement- as a safeguard in the civil law. Where the research aims to clarify what is meant, its basis, and its nature in the civil law and Islamic jurisprudence, with a clarification of the opinions of jurists and court rulings, using this analytical inductive comparative method. The research consists of two chapters, the first of which includes the definition of the right to confinement and its basis in the civil law and Islamic jurisprudence through two topics, while the second chapter contains several topics explaining the nature of the right to confinement in Romanian, French, and Egyptian law, and finally Islamic jurisprudence, and the research ends with a conclusion that includes The most important findings and recommendations. It is clear through the research the agreement of civil law and Islamic jurisprudence in their definition of the meaning of the right to confinement, as well as their agreement in the basis on which it was established, with the uniqueness of Islamic jurisprudence dealing with the broader basis "right to victory, while the opinions of jurists and judges differed in the nature of this right between several directions. The study concluded that he argued that it was not accepted in terms of its nature, which was supported by the Court of Cassation in some of its rulings. It is worth noting that Islamic jurisprudence did not stop much when explaining the nature of the right to confinement, forming a general theory that preceded the positive legislation by applying the right to confinements an original right All- inclusive.
Keywords: القوانين المدنية -- حقوق الإنسان -- الفقه الإسلامية -- مسائل الحبس -- الضمانات القانونية